2020
DOI: 10.1177/0144598720941148
|View full text |Cite
|
Sign up to set email alerts
|

Influences of supercritical carbon dioxide fluid on pore morphology of various rank coals: A review

Abstract: Supercritical carbon dioxide is known to change the pore structure of coals and thus affect their carbon dioxide sequestration capacity. In this study, supercritical carbon dioxide dependence of pore morphology of coals was reviewed. Results indicated that the micropore surface area and volume of dry coals varied between –20% and 20% after exposure to supercritical carbon dioxide. Changes in the micropore size distribution of dry coals after supercritical carbon dioxide exposure were not found to be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 102 publications
(220 reference statements)
0
6
0
Order By: Relevance
“…The calculation of the fractal dimension of the mercury intrusion method can be solved jointly by Washburn's equation and scaling law, 74 or can be based on the Menger model, thermodynamic model, and Sierpinski model. 66,75 66,67 According to Lu et al, 66 the Sierpinski model is able to describe the heterogeneity of seepage pores in tectonically deformed coal and can be used in comparison with the thermodynamic model. The FHH model can characterize the heterogeneity of adsorption pores, while the Sierpinski model can be used as a supplement.…”
Section: Detection Methods For Coal Poresmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculation of the fractal dimension of the mercury intrusion method can be solved jointly by Washburn's equation and scaling law, 74 or can be based on the Menger model, thermodynamic model, and Sierpinski model. 66,75 66,67 According to Lu et al, 66 the Sierpinski model is able to describe the heterogeneity of seepage pores in tectonically deformed coal and can be used in comparison with the thermodynamic model. The FHH model can characterize the heterogeneity of adsorption pores, while the Sierpinski model can be used as a supplement.…”
Section: Detection Methods For Coal Poresmentioning
confidence: 99%
“…In view of the complex pore structure complexities, conventional pore characterization methods are difficult to quantitatively characterize the heterogeneity and complexity of pores . It has been shown that coal pore structure and surface morphology are self-similar in a certain range, and fractal theory has been widely recognized as an effective tool to describe the complexity of coal pore structure. …”
Section: Detection Methods For Coal Poresmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al [11] investigated the seepage law of coal under the action of ScCO 2 and discovered that ScCO 2 triggered the appearance of honeycomb-shaped pores and improved the permeability of the coal body. The coal sample treated with ScCO 2 -H 2 O mainly experienced changes in micropores, while the low-rank coal sample mainly experienced changes in macropores and mesopores [12]. In the experimental study on fracture initiation and extension of ScCO 2 -H 2 O fractured coal, it was observed that ScCO 2 -H 2 O led to the formation of numerous complex laminar bifurcation fractures in the coal body [13].…”
Section: Introductionmentioning
confidence: 99%